IMPLEMENTATION OF VISUAL MATERIALS IN TEACHING SECOND LANGUAGE - Ruziyeva, Nafisa (Центр Научных Публикаций (buxdu.uz), 2024)
Visual aids are powerful tools that can be used to assist the teachers in teaching a foreign language. They can be utilized to add diversity to the classroom activities and effectively display complex teaching material. There are several advantages to employing visuals in the classroom, ranging from capturing and maintaining students' attention to encouraging them to participate actively during the lessons, engage with the topic and assisting them in learning the material.